Design of human-propelled vehicle for sport used - Muhammad Sabri Bin Mohamed Mansor (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
Design of a human propelled vehicle for sport used was a research to study the optimum design that could be implemented as affordable model that can be obtained by user to be used in sport field. The main object of this research was to study the performance of the designed HPV for sport purpose and to design a HPV With the conisideration on aspects of material and exixsting specification.